2022
DOI: 10.1021/acs.jpclett.2c02393
|View full text |Cite
|
Sign up to set email alerts
|

Retarded Charge Recombination to Enhance Photocatalytic Performance for Water-Free CO2 Reduction Using Perovskite Nanocrystals as Photocatalysts

Abstract: Femtosecond transient absorption spectral (TAS) investigations were performed to understand the carrier relaxation mechanism for perovskite nanocrystals Cs1–x FA x PbBr3 (CF, x = 0.45) and CsPbBr3 (CS), which served as efficient photocatalysts for splitting of CO2 into CO and O2 in the absence of water. Upon light irradiation for 12 h, formation of deep trap states was found for both CS and CF samples with spectral characteristics of the TAS photobleach (PB) band showing a long spectral tail extending to the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Net-zero carbon emission has become a critical issue for environmental protection in recent decades due to the intensive consumption of nonrenewable fossil energy by human society, resulting in the global greenhouse effect. Hence, the development of sustainable and renewable approaches for energy production and environmental remediation is important. , In addition, the conversion of CO 2 into value-added chemical products has been demonstrated to be a promising and fascinating technology for addressing the issue of carbon emission. , Photocatalytic CO 2 reduction can directly convert CO 2 and H 2 O into hydrocarbon solar fuels by using semiconductor photocatalysts and endless solar energy, which has been demonstrated to be one promising strategy for solving greenhouse effects and complementing the carbon cycle. In recent years, inorganic lead halide perovskite (ILHP)-based semiconductors have been proven to be a potential candidate to serve as photocatalysts for solar energy conversion because of their remarkable photon harvesting ability toward sunlight, the long diffusion length of photoexcited charge carriers, and tunable energy-band structure by composition modulation. In addition, the formation of ILHP nanoheterostructures (NHSs) presented promising activity in photocatalytic CO 2 reduction. The mechanisms behind the remarkable photoactivity for ILHP NHSs have been proposed as significant charge-separation efficiencies due to the fact that the type-II band structure, Z-scheme, or Step-scheme would facilitate diverse charge transportation at the heterojunction. The separated charge carriers at the different domains of ILHP NHSs would exhibit a higher possibility for carrying out the CO 2 reduction and water oxidation, leading to superior efficiency in photocatalytic CO 2 conversion and better yields of chemical products.…”
mentioning
confidence: 99%
“…Net-zero carbon emission has become a critical issue for environmental protection in recent decades due to the intensive consumption of nonrenewable fossil energy by human society, resulting in the global greenhouse effect. Hence, the development of sustainable and renewable approaches for energy production and environmental remediation is important. , In addition, the conversion of CO 2 into value-added chemical products has been demonstrated to be a promising and fascinating technology for addressing the issue of carbon emission. , Photocatalytic CO 2 reduction can directly convert CO 2 and H 2 O into hydrocarbon solar fuels by using semiconductor photocatalysts and endless solar energy, which has been demonstrated to be one promising strategy for solving greenhouse effects and complementing the carbon cycle. In recent years, inorganic lead halide perovskite (ILHP)-based semiconductors have been proven to be a potential candidate to serve as photocatalysts for solar energy conversion because of their remarkable photon harvesting ability toward sunlight, the long diffusion length of photoexcited charge carriers, and tunable energy-band structure by composition modulation. In addition, the formation of ILHP nanoheterostructures (NHSs) presented promising activity in photocatalytic CO 2 reduction. The mechanisms behind the remarkable photoactivity for ILHP NHSs have been proposed as significant charge-separation efficiencies due to the fact that the type-II band structure, Z-scheme, or Step-scheme would facilitate diverse charge transportation at the heterojunction. The separated charge carriers at the different domains of ILHP NHSs would exhibit a higher possibility for carrying out the CO 2 reduction and water oxidation, leading to superior efficiency in photocatalytic CO 2 conversion and better yields of chemical products.…”
mentioning
confidence: 99%
“…We assign τ 1 , τ 2 , and the nanosecond offset to be associated with processes of shallow trap, bulk trap, and radiative recombination, respectively. 40 Similarly, the transient kinetics of the PB1 band display τ 1 (30 ps), τ 2 (140 ps), and the nanosecond offset for 400 and 600 nm excitations. Note that for the 680 nm excitation, no MAdomain species was excited, and the shallow-trap-mediated recombination (τ 1 ) occurred in 10 ps as probed at 690 nm (Figure 4i), the same as those of PB2 band relaxation probed in the MA domain.…”
mentioning
confidence: 96%
“…We also investigated the optical properties and carrier relaxation dynamics of both PeNCs for the pristine film in a dark, pristine film photoactivated for 12 h and CO 2 adsorbed film photoactivated for 12 h, as the results reported elsewhere. 23 We found that photoactivation significantly enhances the possibility of charge separation and retards the charge recombination so that these photogenerated charge carriers would have more chances to participate in the following catalytic reaction. The comparison between CS and CF samples shows that the CF samples had slower charge recombination than the CS samples for all cases, indicating that the CF sample is more suitable than the CS sample for photocatalytic experiments.…”
mentioning
confidence: 99%
“…The comparison between CS and CF samples shows that the CF samples had slower charge recombination than the CS samples for all cases, indicating that the CF sample is more suitable than the CS sample for photocatalytic experiments. 23 To implement photocatalytic CO 2 reduction for CS and CF PeNCs, we used a reaction setup similar to that previously reported. 14 First, we dispersed PeNC in toluene solution (∼0.3 mL) and evenly dropped the solution at the bottom of the reactor.…”
mentioning
confidence: 99%
See 1 more Smart Citation